TMEM16A is indispensable for basal mucus secretion in airways and intestine. Issue 3 (26th December 2018) - Benedetto, Roberta; Cabrita, Inês; Schreiber, Rainer; Kunzelmann, Karl
ABSTRACT: Transmembrane member 16A (TMEM16A) is the Ca 2+ ‐activated chloride channel in airways and intestine. It has been associated with goblet cell metaplasia, as expression of TMEM16A is strongly up‐regulated in cystic fibrosis and asthma during mucus hypersecretion. However, the possible role of TMEM16A for mucus production or mucus secretion remains obscure, and whether TMEM16A controls the function of intestinal goblet cells is entirely unknown. Basal mucus secretion in lungs occurs through low levels of ATP in the airway surface liquid. Here, we report for the first time that TMEM16A is essential for basal secretion of mucus in airways and intestine. Airway‐ciliated and intestinal epithelial‐specific knockout of TMEM16A ( TMEM16A flox/flox FoxJ1, TMEM16A flox/flox Vil1) leads to accumulation of mucus in airway club (Clara) cells and intestinal goblet cells, respectively. Acute ATP‐induced mucus secretion by airway club cells is inhibited when TMEM16A is knocked out in ciliated cells, possibly as a result of compromised release of prosecretory cytokines. Knockdown or inhibition of TMEM16A in human Calu3 airway epithelial cells indicates compromised IL‐8 release. In intestinal goblet cells lacking expression of TMEM16A, mucus accumulates as a result of compromised ATP‐induced secretion. In contrast, cholinergic mucus secretion by compound exocytosis is independent of TMEM16A. The data demonstrate a previously unrecognized role of TMEM16A for membrane exocytosis and describe a novel, ATP‐driven pathway for intestinal mucus secretion. We conclude that ATP‐dependent mucus secretion in both airways and intestine requires TMEM16A. The present results may form the basis for a novel, therapeutic approach for the treatment of mucus hypersecretion in inflammatory airway and intestinal disease.—Benedetto, R., Cabrita, I., Schreiber, R., Kunzelmann, K. TMEM16A is indispensable for basal mucus secretion in airways and intestine. FASEB J. 33, 4502–4512 (2019). www.fasebj.org